Can the number of functional teeth potentially affect cognitive function? - Cho, Min-Jeong; Kim, Ji-Young; Jung, Yun-Sook; Shin, Hae-Eun; Youn, Ha-Young; Park, Tae Jun; Choi, Youn-Hee; Song, Keun-Bae (Journal of Korean Academy of Oral Health, 2018)
Objectives: With the growing elderly population, there is an increasing interest in the oral and general health of elderly individuals. Loss of teeth is representative of oral disease in elderly individuals and is associated with medical and dental problems. The purpose of this study was to investigate the relationship between the number of remaining functional teeth and cognitive function. Methods: A total of 456 (111 public health centers, 261 senior centers, 84 sanatoriums) older adults (aged ≥65 years) residing in Korea were included. A mental health nurse examined the cognitive function using the Korean version of the Mini-Mental State Examination. A dentist examined the number of functional teeth and denture status through an oral examination, while a dental hygienist surveyed the subjective masticatory level using a questionnaire. Results: The mean age of the participants was 79.5 years (range 65-97 years), and 76.1% of them were women. Participants with a small number of functional teeth had lower cognitive function. In these participants, the odds ratio with poor cognitive function was 2.30 times higher; it was 2.74 times higher after adjusting for age, sex, residence, education, and denture use, and was statistically significant. Conclusions: Our study suggested that the number of functional teeth was associated with cognitive function in the Korean elderly population. KCI Citation Count: 0